Legal Protection Against Peer-to-Peer Lending-Based Financial Technology Losses: An Analysis of Islamic Law Contracts and Positive Law - Abdillah; Sukmawati; Syah, Muhammad Fadly (Mazahibuna: Jurnal Perbandingan Mazhab, 2022)
This article discusses the analysis of Islamic legal contracts and positive laws concerning the legal protection against financial technology losses based on peer-to-peer lending. This discussion is based on two raised subtopics namely 1) The importance of legal protection against the losses of the parties involved in this transaction and 2) The analysis regarding the contract used in this transaction, which is based on two perspectives, the Islamic legal contracts and positive law. Furthermore, this qualitative research uses a comparative approach. The data analyzed in this study were both primary and secondary. The primary and secondary data were collected from interviews conducted via different platforms with various related sources and from materials, such as journals, articles, and theses, respectively. The results of this study show the importance of legal protection for every party involved in peer-to-peer lending-based financial technology transactions. Some legal issues that have been frequently experienced, include defaults, misuse of personal data, and even the threat of terror received by debtors. Additionally, reviews regarding the contract in the transaction imposed by the organizer were based on 2 perspectives, namely Islamic law and positive law. The transaction process will only become illegal when it conflicts the Islamic laws with the elements of usury and interest in it. And based on the perspective of positive law itself, if there is a defect or anything contrary to decency or public order, the agreement or contract becomes null and void.